Exposure to Internet Pornography: A Cross-sectional Study among Primary School-aged Children in Java - Ratih Indraswari; Bagoes Widjanarko; Riza Hayati Ifroh (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: In today's times, generation Z has extraordinary skills in finding information. This generation is very good at using gadgets to learn, play, and even earn their own income. Pornographic content often appears accidentally and begins to be known by children. Curiosity is often the reason teenagers access pornography and then end up with the practice of premarital sexual intercourse. This study aims to understand how primary school-age children behave in accessing pornographic content. Methods: This cross-sectional study sampled 63 students in fifth grade at a public primary school, using by total population sampling technique. Data was collected using a self-administered questionnaire technique. The data obtained were then analyzed using univariate analysis and linear regression. Results: Most respondents in this study were 11-year-olds (82.5%), comprising 41.3% boys and 58.7% girls, and not experienced puberty yet (60.3%). Of 39.7% have been accessing porn through handphone (41.3%) and laptop (1.6%). As many as 3.2% of children have accessed pornography since the age of < 7 years. About 17.5% of pornographic content accessed is in real motion. The content accessed is mostly pictures of naked people and kissing scenes. As many as 19% of children admitted to accessing pornography accidentally and immediately closed the access. Conclusion: The health department of Family Health and School Health needs to partner with parents to improve supervision and communication between parents and children. Providing healthy living skills training for children needs to be embedded into the educational curriculum so that skills can be carried out routinely and continuously.